Low memory image stitching and compression for WMSN using strip–based processing. (23rd January 2012) - Chia, Wai Chong; Chew, Li Wern; Ang, Li–Minn; Seng, Kah Phooi
Due to the limited Field–Of–View (FOV) of a single camera, it is sometimes desired to extend the FOV using multiple cameras. Image stitching is one of the methods that can be used to exploit and remove the redundancy created by the overlapping FOV. However, the memory requirement and the amount of computation for conventional implementation of image stitching are very high. In this paper, this problem is resolved by performing the image stitching and compression in a strip–by–strip manner. First, the stitching parameters are determined by transmitting two reference images to an intermediate node to perform the processing. Then, these parameters are transmitted back to the visual node and stored in there. These parameters will be used to determine the way of stitching the incoming images in a strip–by–strip manner. After the stitching of a strip is done, it can be further compressed using a strip–based compression technique.